AB0322 LESSONS LEARNED FROM THE PAST THAT SHOULD IMPROVE THE FUTURE: 18 YEARS OF EXPERIENCE WITH BIOLOGIC THERAPIES IN RHEUMATOID ARTHRITIS IN A TERTIARY RHEUMATOLOGY CENTER IN ROMANIA. (2nd June 2020) - Serban, T.; Satulu, I.; Badea, I.; Mihai, C.; Badea, D.; Vutcanu, O.; Martin, A.; Milicescu, M.; Udrea, G.; Bojinca, M.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease, which affects approximately 1% of the population. Although diagnostic, monitoring and treatment strategies have improved noticeably over the last decades, allowing an early and sustained clinical and radiological remission, both direct and indirect costs of treatment and disease still create an economic burden for patients and society. The last few years have brought many therapeutic options and knowledge about them, which has led to the 2019 updated EULAR recommendations for the management of RA (1). Objectives: This study aimed to evaluate the trends in prescribing of biologic therapies in RA over time, the factors that influenced them and the persistence of patients on these treatments. Methods: In this retrospective study we evaluated patients with RA treated with biologic therapies in the last 18 years, who presented for routine clinical and biological evaluation, performed according to the standard of care principles in RA. Results: 244 patients were enrolled in this study. Baseline characteristics are presented in Table 1 . There is a significant decrease in the persistence period on the first biological therapy after 2010 (60.67 ± 50.53 months before 2010 vs. 37.02 ± 34.92 months after 2010, p <0.001, 95% CI = - 34, 464 - -12, 838). There is a significant increase in the period from diagnosis to the initiation of biological therapy after 2012 (6.88 ± 6.75 years before 2012 vs. 9.25 ± 9.33 years after 2012, p <0.001, 95% CI = 0.341-4.406). Overall, regardless of the therapeutic line in which they were used, persistence on anti-CD20 (44, 89±43, 02 months (mean±SD)) therapies was significantly higher than that on TNFi (81, 85±42, 17 months (mean±SD)) (p<0, 001, CI=27.806-46.129). (Image 1) Conclusion: The two trends observed in this study: the decrease in persistence on biologic therapy, in 2010, and the increase of the period between RA diagnosis and the initiation of a biologic therapy, in 2012, were generated by the appearance of new molecules, thus reducing the boundaries generated by the previously limited number of options, and by the major changes in national health insurance system regulations. Anti-CD20 therapy proved to be non-inferior to TNFi therapies regarding persistence on therapy and did not result in higher adverse events than TNFi, justifying the inclusion of RTX therapy as one of the biological therapies used in the first line in 2019 RA treatment recommendations. A limitation of this study is the small number of patients who received other therapies (JAKi, T cell co-stimulation blockers, anti IL6), which did not allow a correct analysis of other therapeutic lines compared to those previously mentioned. References: [1]Smolen JS, et al. Ann Rheum Dis 2020;0:1–15. doi:10.1136/annrheumdis-2019-216655 Disclosure of Interests: None declared